Vaccine‐preventable disease following allogeneic haematopoietic stem cell transplant in Western Australia. (5th September 2018) - Ryan, Anne L; Kerr, Fiona; Gough, Hazel; Carter, Tina L; Kotecha, Rishi S
Abstract : Aim: Infection is an important and frequent cause of mortality and morbidity following allogeneic haematopoietic stem cell transplantation (HSCT). This study was conducted to determine the epidemiology and clinical phenotype of vaccine‐preventable disease in children who have undergone HSCT following the implementation of a standard revaccination programme. Methods: Children receiving first allogeneic HSCT in Western Australia between January 2005 and December 2014 were eligible for recruitment. Patients received standard antimicrobial prophylaxis and were vaccinated according to the West Australian post‐HSCT immunisation schedule, commencing 6 months following HSCT. Children who developed any illness post‐HSCT were reviewed, and investigations for infectious disease were undertaken as clinically indicated. Positive identification of vaccine‐preventable disease was documented with the clinical course of the illness. Results: A total of 71 patients were enrolled in the study. The overall incidence of vaccine‐preventable disease following HSCT was 19.7%; influenza accounted for 50% of all cases, herpes zoster for 42.9%. All episodes occurred late, beyond day 100 post‐HSCT. Overall survival for matched‐sibling donor transplants was 83.3 and 75.0% at 1 and 5 years, respectively, and was 72.3 and 63.3% for alternative donor transplants. Mortality due to vaccine‐preventable disease was low, with one death from disseminated herpes zoster. Conclusions: There is a high incidence of vaccine‐preventable morbidity post‐allogeneic HSCT in West Australian children. Viral aetiology constitutes the main burden, namely, influenza infection and varicella zoster virus reactivation. Further efforts are required to identify the most appropriate preventative strategies.